The Impacts of COVID-19 Pandemic to the Welfare of Indonesian Musicians - Sundari, Olivia Evelin; Putri, Kezia Karnila (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research discussed the welfare of Indonesian musicians during the COVID-19 outbreak. Since the outbreak in March 2020, the Indonesian government had implemented large-scale social restrictions in major cities, aiming to minimize the spread of the disease. Restrictions included the temporary termination of onsite events (concerts and festivals) and a shift from offline to online education, including music classes. With few references provided about Indonesian musicians’ welfare, it intended to present valid data to comprehend better the phenomena that would expectantly lead to appropriate and targeted support. From September to October 2020, an online survey of musicians across Indonesia to identify the impact of the COVID-19 pandemic on their overall welfare was done. The 581 respondents from all provinces of Indonesia participated in this survey. The respondents included 54% full-time musicians and 46% part-time musicians. The researchers divided the identified impacts into two categories: direct and indirect impacts, encompassing various aspects, including changes in mental health, working platforms, and financial issues. The survey indicates that 71,6% of respondents have experienced changes in their daily life patterns. Online working methods increase from 8,3% to 72,5%, whereas offline methods decrease from 92,4% to 17,6%. Aside from those changes, respondents with income below one million rupiahs increase sharply from 9% (before the pandemic) to 47% (after the pandemic). Utilizing Chi-square independence tests on SPSS v. 26, this descriptive study finds a significant association between working status (full-time or part-time musicians) and their responses to the impact of the COVID-19 pandemic on their lives.